Nickel: A Micronutrient Essential for Higher Plants - Brown, Patrick H. (1987)
Nickel was established as an essential micronutrient for the growth of temperate cereal crops. Grain from barley (Hordeum vulgare L. cv `Onda'; containing 40 to 80 nanograms of Ni per gram dry weight) grown in solution culture with negligible Ni concentrations (< 30 nanograms of Ni per liter) exhibited greatly reduced germination rates (i.e. 50% less than grain from Ni-adequate plants) and seedling vigor of the viable grain was greatly depressed. Grain containing less than 30 nanograms per gram dry weight was inviable. Under Ni-deficient conditions, barley plants fail to produce viable grain because of a disruption of the maternal plant's normal grain-filling and maturation processes that occur following formation of the grain embryo. The observations that (a) barley plants fail to complete their life cycle in the absence of Ni and (b) addition of Ni to the growth medium completely alleviates deficiency symptoms in the maternal plants satisfies the essentiality criteria; thus, Ni should be considered a micronutrient for cereals. Because Ni is required by legumes, and is now established as essential for cereals, we conclude that Ni should be added to the list of micronutrients essential for all higher plant growth.